HUBUNGAN PENGETAHUAN GIZI DAN KONSUMSI LEMAK DENGAN KEJADIAN OBESITAS SENTRAL PADA IBU RUMAH TANGGA DI KELURAHAN SIDOMULYO BARAT - Nopri Yanto; Besti Verawati; Faridatul Akmalia (Universitas Pahlawan, 2019)
Central obesity if the increase of body fat which its location is at abdominal area (stomach) and can cause various degenerative diseases such as hypertension, diabetes mellitus type 2, and cardiovascular disease. The purpose of this research is to analyze the correlation between nutrition knowlege and fat consumption with central obesity occurance on housewives at West Sidomulyo Village in 2019. The type of this research was quantitative research with Cross-Sectional Design. The population of this research were 856 housewives age â‰¥ 35 years old at West Sidomulyo Village with total samples 169 people selected by using Purposive Sampling. The technique of data collection was questionnaire on nutrition knowledge and Food Recall 2x24 hours, stomach circumference measurement (LP), body weight, and body height. Data analysis was by using Chi-Square test. The results of univariate analysis show that almost half of respondents have good knowledege on nutrition (46.2%), almost half of respondents consume more fat (40.8%), and most of respondents experience central obesity (68%). The results of bivariate analysis with Chi-Square Test show that there is no significant correlation between nutrition knowledge and central obesity occurance (p=0.074), and there is significant correlation between fat consumption and central obesity occurance (p=0.001). Therefore, it is expected that the society consumes fat in line with their needs and always control their body weight and stomach circumference to stay normal.